Effects of plasticizer diisobutyl adipate on the Japanese medaka (Oryzias latipes) endocrine system - Horie, Yoshifumi; Ramaswamy, Babu Rajendran; Ríos, Juan Manuel; Chee, Kong Yap; Okamura, Hideo (John Wiley and Sons, 2023)
Plasticizer pollution of the water environment is one of the world's most serious environmental issues. Phthalate plasticizers can disrupt endocrine function in vertebrates. Therefore, this study analyzed thyroid-related, reproduction-related, and estrogenresponsive genes in Japanese medaka (Oryzias latipes) to determine whether nonphthalate diisobutyl adipate (DIBA) plasticizer could affect endocrine hormone activity or not. Developmental toxicity during fish embryogenesis was also evaluated. At a concentration of 11.57 mg/l, embryonic exposure to DIBA increased the mortality rate. Although abnormal development, including body curvature, edema, and lack of swim bladder inflation, was observed at 3.54 and 11.57 mg/l DIBA, growth inhibition and reduced swimming performance were also observed. In addition, DIBA exposure increased the levels of thyroid-stimulating hormone beta-subunit (tshβ) and deiodinase 1(dio1) but decreased the levels of thyroid hormone receptor alpha (trα) and beta (trβ). These results suggest that DIBA has thyroid hormone-disrupting activities in fish. However, kisspeptin (kiss1 and kiss2), gonadotropin-releasing hormone (gnrh1), folliclestimulating hormone beta (fshβ), luteinizing hormone beta (lhβ), choriogenin H (chgH), and vitellogenin (vtg1) expression did not change dose-dependently in response to DIBA exposure, whereas gnrh2 and vtg2 expression was elevated. These results indicate that DIBA has low estrogenic activity and does not disrupt the endocrine reproduction system in fish. Overall, this is the first report indicating that non-phthalate DIBA plasticizer is embryotoxic and disrupt thyroid hormone activity in fish.